Mainstreaming CSA into the West African Agricultural Productivity Program - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Since its launch in October 2017, a 2-year project of 2,550,230 US$ funded by the West African Agricultural Productivity Program facilitated by CORAF/WECARD entitled “Capacitating Stakeholders in Using Climate Information for Enhanced Resilience in the Agricultural Sector in West Africa (CaSCIERA-TA)” is expanding approaches, tools, knowledge and skills in CSA developed by the regional team to Benin, Guinea, Mali, Niger and Togo in two communes per country. Choices of CSA options are done based on past, prevailing and projected climate.